Importance of Food Chapter of Murphy’s Repertory (Homoeopathy for All, 2025)
The selection of an appropriate  homoeopathic remedy is guided  by the identification of striking,  singular and peculiar symptoms,  as emphasized by Dr. Hahnemann  in the Organon of Medicine.  Among these, food desires and  aversions serve as key indicators in  individualizing a case and forming  the totality of symptoms. Various  repertories, including those by  Dr. Kent, Dr. Boenninghausen,  Dr. Boger and Dr. Guernsey,  categorize these rubrics differently.  Dr. Robin Murphy’s Homoeopathic  Medical Repertory uniquely  compiles food-related rubrics in a  dedicated ‘Food’ chapter, offering  a structured approach to analyzing  desires, aversions, aggravations,  and ameliorations related to food  and drink. This article explores the  significance of the Food chapter in  Murphy’s Repertory, comparing its  approach to other repertories and  highlighting its clinical utility in  homoeopathic practice.
Keywords: Homoeopathy; Repertory